2002
DOI: 10.1046/j.1365-2567.2002.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen binding to GM1 ganglioside results in delayed presentation: minimal effects of GM1 on presentation of antigens internalized via other pathways

Abstract: SUMMARYPlasma membrane rafts are sphingolipid-and cholesterol-rich patches that function as membrane trafficking and surface signalling regions. Ganglioside G M1 is an integral component of these microdomains, and Escherichia coli enterotoxin B subunit (EtxB) is a pentamer that binds with high affinity to G M1 resulting in G M1 cross-linking. We previously demonstrated that antigen coupled directly to EtxB resulted in enhanced presentation relative to antigen taken up by fluid-phase endocytosis. Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The combination of increased cell viability and reduced activation could prolong the antigen presentation capacity of DC and consequently manifest as an adjuvant effect because of increased T cell activation. Indeed, this interpretation is not without precedent, as similar reports of EtxB increasing the viability and survival of B cells and macrophages for delayed antigen presentation have been reported [14,39]. An alternative interpretation of the in vitro results could be that an increase in cell viability and a reduction in expression of activation markers is because of increased maturation of DC.…”
Section: Discussionmentioning
confidence: 86%
“…The combination of increased cell viability and reduced activation could prolong the antigen presentation capacity of DC and consequently manifest as an adjuvant effect because of increased T cell activation. Indeed, this interpretation is not without precedent, as similar reports of EtxB increasing the viability and survival of B cells and macrophages for delayed antigen presentation have been reported [14,39]. An alternative interpretation of the in vitro results could be that an increase in cell viability and a reduction in expression of activation markers is because of increased maturation of DC.…”
Section: Discussionmentioning
confidence: 86%
“…For OVA in the fluid phase, such an impact on the cytoskeleton would conceivably enhance its uptake and presentation. However, in a previous study it was found that incubation of A20 WT B cell with LT-IB did not noticeably enhance OVA presentation when added in the fluid phase [19]. In the latter study, the response of DO.11.10 T cells to OVA was evaluated by measuring the level of proliferation of IL-2-responsive HT-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LT-IB and LT-IIaB were used at 5μg/ml and 2.5μg/ml, respectively, unless indicated otherwise. The choice of LT-IB and LT-IIaB doses in this study is based on their direct or indirect stimulatory effect on immune cells and their products, as shown previously [13, 14, 19, 22]. LT-IIbB and LT-IIbB(S74D) were used at 10 μg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations